Vladavina prava i legitimnost upravnih sudaca - Đerđa, Dario (Array, 2019)
The way in which the Republic of Croatia founds the legitimacy of judiciary duties and thereby enhances the rule of law is analyzed in this paper. It is aimed in particular at the legitimacy of administrative judges upon resolving administrative disputes and passing judgements. To this aim, the independence of administrative judges is considered as well as the mechanisms to which the independence of judicial powers contribute. Then, the way judges are appointed is analyzed, which results in whether citizens can trust the judges’ expertise and moral values. Also analyzed is the mechanism for establishing the expertise of judges through evaluating judges' implementation of duties. Finally, the legitimacy of administrative judges' decisions is also considered through the composition of the court in first instance administrative judicial decisions and through the trust given by citizens in the resolution of administrative disputes according to the individual judge. How administrative court judges in the Republic of Croatia are appointed and assessed in the same way as judges of other regular or specialized courts and how the question of independent implementation of judicial duties correlates regardless of the court wherein the judge is appointed for judicial duty make up a large part of the conclusions related to all judges in the Republic of Croatia. This paper therefore in some way exceeds the very problem area of rule of law and administrative judge legitimacy.